Analysis of the Atlantic salmon genome reveals a cluster of Mx genes that respond more strongly to IFN gamma than to type I IFN - Robertsen, Børre; Greiner-Tollersrud, Linn; Jørgensen, Lars Gaute (Developmental & Comparative Immunology, 2018)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. Mx proteins are antiviral GTPases, which are induced by type I IFN and virus infection. Analysis of the Atlantic salmon genome revealed the presence of 9 Mx genes localized to three chromosomes. A cluster of three Mx genes (SsaMx1 – SsaMx3), which includes previously cloned Mx genes, is present on chromosome (Chr) 12. A cluster of five Mx genes (SsaMx4-SsaMx8) is present on Chr25 while one Mx gene (SsaMx9) is present on Chr9. Phylogenetic and gene synteny analyses showed that SsaMx1-SsaMx3 are most closely related to the main group of teleost Mx proteins. In contrast, SsaMx 4-SsaMx9 formed a separate group together with zebrafish MxD and MxG and eel MxB. The Mx cluster in Chr25 showed gene synteny similar to a Mx gene cluster in the gar genome. Expression of Mx genes in cell lines stimulated with recombinant IFNs showed that Mx genes in Chr12 responded more strongly to type I IFN than to type II IFN (IFN gamma) whilst Mx genes in Chr25 responded more strongly to IFN gamma than to type I IFNs. SsaMx9 showed no response to the IFNs.